Stem Cells in Burn Eschar - Vincent C. Van Der Veen; Marcel Vlig; Florine J. Van Milligen; Sharon I. De Vries; Esther Middelkoop; Magda M. W. Ulrich (Cell Transplantation, 2012)
This study compares mesenchymal cells isolated from excised burn wound eschar with adipose-derived stem cells (ASCs) and dermal fibroblasts in their ability to conform to the requirements for multipotent mesenchymal stem cells (MSCs). A population of multipotent stem cells in burn eschar could be an interesting resource for tissue engineering approaches to heal burn wounds. Cells from burn eschar, dermis, and adipose tissue were assessed for relevant CD marker profiles using flow cytometry and for their trilineage differentiation ability in adipogenic, osteogenic, and chondrogenic conditions. Although the different cell types did not differ significantly in their CD marker expression, the eschar-derived cells and ASCs readily differentiated into adipocytes, osteoblasts, and chondrocytes, while dermal fibroblasts only exhibited some chondrogenic potential. We conclude that the eschar-derived mesenchymal cells represent a population of multipotent stem cells. The origin of the cells from burn eschar remains unclear, but it is likely they represent a population of adult stem cells mobilized from other parts of the body in response to the burn injury. Their resemblance to ASCs could also be cause for speculation that in deep burns the subcutaneous adipose tissue might be an important stem cell source for the healing wound.